Faktor-faktor yang Berhubungan dengan Perilaku Pacaran Remaja di SMKN 2 Sewon - Chandra Ariani Saputri; Fatmawati F (PT.Mantaya Idea Batara, 2022)
Adolescence is a transition from childhood to adulthood. Adolescence is a stage where they experience a change in thinking (mindset), self-identity questing, and curiosity increase. The influence of globalization causes behavioral changes in adolescents including dating behavior. The study aims to investigate the factors related to adolescents’ dating behavior in SMK N/ State Vocational High School 2 of Sewon. The study employed quantitative method and descriptive correlative design with cross sectional time approach. The samples in this study were 50 adolescents. The sampling technique was Purposive Sampling that fulfill the inclusion and exclusion criteria. The primary data were collected using questionnaire. The data were analyzed using Chi-Square. The result shows that 31 (62%) of adolescents have high religiosity, 26 (52%) of adolescents have negative peer roles, and 26 (52%) of adolescents have positive parenting roles. The variables of religiosity, the role of peers, and the role of parents are shown to be related to the adolescents’ dating behavior with p value ? 0.05. Hence, in this case the adolescent should keep the friendship environment and should be more active in positive activities. Meanwhile, the schools are suggested to initiate the Center for Information and Youth Counseling.